Looking into the Language Status of Osing with Contrastive Analysis of the Basic Vocabulary of Osing and Malang Javanese - Ika Nurhayani; Hamamah Hamamah; Dwi Ira Ningrum; Ressi Maulidina Delijar (PAROLE: Journal of Linguistics and Education, 2020)
Osing is a language spoken by the majority of people in Banyuwangi, East Java. However, there is obscurity on its status whether it is considered as one of the Javanese dialects or as an independent language originated in Java. Some noted that the Osing is another version of Javanese, while the people living in the Banyuwangi Region regard the Osing as a distinct identity that differentiates it from the rest of the Javanese speaking regions in Central and East Java. Hence, this research aims to provide linguistic evidence on the lexical differences between the Osing and Malang Javanese. The research is significant because there is no previous research that provides linguistic evidence on the differences between the Osing and other Javanese dialects. Data of this study was obtained through eliciting the production of the basic vocabulary of the Osing and Malang Javanese speakers. The findings of the research provide evidence to the observation of previous linguists in that the Osing is not a linguistically separate language of Javanese.